Beat the Heat: Effects of a Motivational Self-Talk Intervention on Endurance Performance. Issue 4 (2nd October 2018) - Hatzigeorgiadis, Antonis; Bartura, Khelifa; Argiropoulos, Christos; Comoutos, Nikos; Galanis, Evangelos; D. Flouris, Andreas
Abstract : The study examined the effects of a motivational self-talk intervention on endurance cycling performance in hot conditions. Participants were 16 physically active adult men. After a baseline VO2 peak assessment and two training sessions, participants completed a 30 min cycling trial in a hot environment (35°C, 45% relative humidity) while maintaining a steady rate of perceived exertion. Participants of the intervention group produced greater power output during the final third of the trial. Findings suggest that the self-talk strategy seems to have compromised the aversive effects of the demanding environmental conditions and provide support for the psychobiological model of endurance performance.